Content Language Integrated Learning (CLIL) and Non Native English Speaking (NNES) Learners English Language Acquisition - Senorica Yulia Sari (Journal of English Language Teaching, 2023)
This essay aims to outline the potential of the CLIL method in helping Non Native English Speaking (NNES) students studying in Anglosphere countries to optimize their English competence. Existing literature were analysed to explore how CLIL also plays a role in developing students’ English learning while they are comprehending subjects’ content. These studies show that CLIL has a positive relationship with students’ motivation; thus, it can develop their English ability.  Moreover, CLIL has the Triptych concept or three interrelated aspects of language processing: language for learning, language of learning, and language through learning. These perspectives reflect how language can be integrated thoroughly into certain subjects with more time compared to the length of time in traditional classrooms. This essay aims to outline the potential of the CLIL method in helping Non Native English Speaking (NNES) students studying in Anglosphere countries to optimize their English competence. Existing literature were analysed to explore how CLIL also plays a role in developing students’ English learning while they are comprehending subjects’ content. These studies show that CLIL has a positive relationship with students’ motivation; thus, it can develop their English ability.  Moreover, CLIL has the Triptych concept or three interrelated aspects of language processing: language for learning, language of learning, and language through learning. These perspectives reflect how language can be integrated thoroughly into certain subjects with more time compared to the length of time in traditional classrooms.